2014
DOI: 10.3109/0886022x.2014.949766
|View full text |Cite
|
Sign up to set email alerts
|

Picroside II decreases the development of fibrosis induced by ischemia/reperfusion injury in rats

Abstract: In kidney transplantation, renal ischemia and reperfusion injury was one of the leading factors to the development of renal fibrosis, which was the main cause of graft loss. The fibrogenic changes were associated with the long term inflammation elicited by ischemia and reperfusion injury. In the present study, we investigated the role of the Picroside II, the main active constituents of the extract of picrorrhiza scrophulariiflora roots, in attenuating renal fibrosis in a renal ischemia and reperfusion injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…hepatoprotective and choleretic effects [3,4], protective effects against neuronal cell injury [5], protective effects against myocardial apoptosis [6,7], and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…hepatoprotective and choleretic effects [3,4], protective effects against neuronal cell injury [5], protective effects against myocardial apoptosis [6,7], and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that picroside II is capable of protecting the heart or kidney from I/R-induced injury by inhibition of the inflammatory response (15,16). These studies suggested that picroside II has an anti-inflammation property.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat model of middle cerebral artery occlusion and reperfusion, pretreatment with picroside II could significantly improve the neurobehavioral function and inhibit neurocyte apoptosis, which was correlated with a decrease of inflammatory factor production by inhibition of the TLR-4/NF-κB signaling pathway (15). In addition, the study by Wang et al (16) demonstrated that picroside II was able to decrease I/R-induced renal fibrosis in rats by inhibition of long-term inflammation. Recently, it has been reported that picroside II has a protective effect on myocardial I/R injury in rats (17).…”
Section: Introductionmentioning
confidence: 99%
“…Picroside as an active ingredient of Picrorhiza scrophulariiflora, is iridoid glycoside, which has many pharmacological activities such as liver‐protective and choleretic effect, anti‐tumor and anti‐diabetics and so on [1] . The Picroside II (PII, Figure 1) as the main component has multiple pharmacological effects, including anti‐apoptosis, [2] anti‐inflammatory, [3] anti‐cancer, [4] anti‐oxidation, [5] anti‐virus, [6] neuroprotection, [7,8] myocardial protection, [9,10] kidney protection, [11] liver protection, [12] cerebral ischemic injury protection, [13] anti‐bone resorption [14] and so on.…”
Section: Introductionmentioning
confidence: 99%